Immunological Traits of Cryoablation in Combination Therapy of Cancer - Goltsev, Anatoliy M.; Bondarovych, Mykola O.; Dubrava, Tatiana G.; Babenko, Natalya M.; Gaevska, Yuliya O.; Ostankov, Maksim V.; Buriak, Iryna A. (Problems of Cryobiology and Cryomedicine, 2019)
Cryoablation is a method of choice in treatment of solid tumors of diï¬€erent localization. In addition to the destruction of pathological tissue, the cryoablation causes to complex changes in the immune system. This paper brieï¬‚y discusses the implementation of the abscopic eï¬€ect after cryosurgery of tumors, as well as possible changes in the immune system that accompany it. The abscopic eï¬€ect is achieved with a release of antigens from the destroyed cells, which trigger a cascade of immune reactions. This article summarizes the results of the combined use of cryoablation and immunotherapeutic methods, in particular adoptive therapy. The introduction of dendritic cells in combination with cryoablation can signiï¬cantly enhance antitumor immunity and reduces the risk of relapse. Â Probl Cryobiol Cryomed 2019; 29(4):Â 297-302